Socialization and Training on Making Compost Fertilizer at Al-Azhaar Islamic Vocational School Tulungagung from Organic Waste - Rohmatul Faizah; Nur Qomariyah Deviyanti; Dina Riska Triswanti; Ekafianda Azzhara Suprapto (Nusantara Science and Technology Proceedings, 2023)
Organic waste is leftover material or rubbish that can be recycled and comes from living creatures, such as food waste, waste from living creatures, or plant waste. Research shows that organic waste can be useful as compost which can be used as plant fertilizer and soil fertilizer. This activity was carried out at the Islamic Boarding School Innovation Thematic KKN activity at Al-Azhaar Islamic Boarding School, Tulungagung. The tools and materials used in socialization and training activities are compost bags, measuring cups, latex gloves, dry leaves, vegetable waste and water. Socialization and training activities are carried out in stages, namely preparing the location as well as the tools and materials that will be used. The location used in this activity is the Al-Azhaar Islamic Vocational School field in Tulungagung. Student and female representatives came forward to practice making compost according to the example given. Question and answer session by students of Al–Azhaar Islamic Vocational School, Tulungagung. The aim of carrying out socialization and training on making compost from organic waste is so that students and students of the Islamic Vocational School Al - Azhaar Tulungagung are able to process organic waste around the school which can be used into more useful items in the form of compost fertilizer.